The evolution of International business 1800-1945. Volume I : British investments in Latin America, 1822-1949 - Rippy, J. Fred (James Fred), 1892- (London ; New York : Routledge, 2000)
General survey of British investments in Latin America. Country-by-country inspection of the British investment. The crux of the matter in global setting.
Keywords: Economics; Investments; Investments, British -- Latin America